2002
DOI: 10.1111/j.1567-1364.2002.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

The three zinc-containing alcohol dehydrogenases from baker's yeast,Saccharomyces cerevisiae

Abstract: This review is a summary of our current knowledge of the structure, function and mechanism of action of the three zinc-containing alcohol dehydrogenases, YADH-1, YADH-2 and YADH-3, in baker's yeast, Saccharomyces cerevisiae. The opening section deals with the substrate specificity of the enzymes, covering the steady-state kinetic data for its most known substrates. In the following sections, the kinetic mechanism for this enzyme is reported, along with the values of all rate constants in the mechanism. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 64 publications
11
85
2
2
Order By: Relevance
“…It was proposed that the increase in the activity of ethanol dehydrogenase with zinc as a cofactor (Leskovac et al, 2002) accounts for enhanced ethanol production (Chandrasena and Walker, 1997). However, in the present work, it was found that there was no excretion of pyruvate, indicating that the enzymes controlling the pyruvate node could be enhanced by zinc supplementation and the pyruvate synthesized upstream might be metabolized quickly at the sub-nodes to the acetaldehyde and oxaloacetate pathways.…”
Section: Impact On the Production Of Biomass And Extracellular Metabocontrasting
confidence: 69%
“…It was proposed that the increase in the activity of ethanol dehydrogenase with zinc as a cofactor (Leskovac et al, 2002) accounts for enhanced ethanol production (Chandrasena and Walker, 1997). However, in the present work, it was found that there was no excretion of pyruvate, indicating that the enzymes controlling the pyruvate node could be enhanced by zinc supplementation and the pyruvate synthesized upstream might be metabolized quickly at the sub-nodes to the acetaldehyde and oxaloacetate pathways.…”
Section: Impact On the Production Of Biomass And Extracellular Metabocontrasting
confidence: 69%
“…In the sample prepared with knocked-out ADH1, the ethanol content reached a value of 0.62% (v/v). However, this value, due to the presence of four other isoforms, may not be stable in other strains of brewing yeast with the same mutation 7 . Considerably higher concentrations of residual saccharides in the beer, or more generally high residual extract values, could pose a problem, but the presence of organic acids, such as lactate and citrate, has a protective effect against bacterial contamination.…”
Section: Discussionmentioning
confidence: 95%
“…The alcohol dehydrogenase lyophilized powder from Saccharomyces cerevisiae (Sigma-Aldrich A7011) (ADH) was used with no further purification. This enzyme has a molecular weight 141-151 kDa, an isoelectric point between 5.4-5.8 and the optimal pH is reported to be in the range of 8.6 and 9.0 [17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…The ADH (alcohol dehydrogenase) is a zinc-containing enzyme, usually used in the food industry [17]. The Saccharomyces cerevisiae produced three isoenzymes of alcohol dehydrogenase, YADH-1 (expressed during anaerobic fermentation), YADH-2 (cytoplasmic form repressed by glucose) and YADH-3 (found in mitochondria) [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation